2012
DOI: 10.1021/la301104a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Nanoparticle–Protein Corona on Colloidal Stability and Protein Structure

Abstract: In biological fluids, proteins may associate with nanoparticles (NPs), leading to the formation of a so-called "protein corona" largely defining the biological identity of the particle. Here, we present a novel approach to assess apparent binding affinities for the adsorption/desorption of proteins to silver NPs based on the impact of the corona formation on the agglomeration kinetics of the colloid. Affinities derived from circular dichroism measurements complement these results, simultaneously elucidating st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
293
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(308 citation statements)
references
References 61 publications
(143 reference statements)
10
293
1
Order By: Relevance
“…By modifying the surface of nanoparticles, the corona shell can change the interactions they have with cells as well as physical and chemical properties of the systems [146,[151][152][153]. In the specific case of Ag NPs, formation of a corona has been shown to increase their colloidal stability in presence of salts [154] and their resistance toward acidic dissolution [155,156]. In 2013, Gnanadhas et al showed that the presence of proteins in the incubation medium led to a lower antibacterial activity of silver nanoparticles [157].…”
Section: Interaction With a Bacterial Culturementioning
confidence: 99%
“…By modifying the surface of nanoparticles, the corona shell can change the interactions they have with cells as well as physical and chemical properties of the systems [146,[151][152][153]. In the specific case of Ag NPs, formation of a corona has been shown to increase their colloidal stability in presence of salts [154] and their resistance toward acidic dissolution [155,156]. In 2013, Gnanadhas et al showed that the presence of proteins in the incubation medium led to a lower antibacterial activity of silver nanoparticles [157].…”
Section: Interaction With a Bacterial Culturementioning
confidence: 99%
“…[89b] Similarly, Gebauer et al reported that the protein corona formed around silver NPs could be utilized to stabilize the particles against agglomeration. [94] In contrast, Au NPs can aggregate when exposed to cellconditioned media (media that has been previously exposed to cells, which alters its composition, for example through growthrelated depletion and secretion of biomolecules). [95] The protein corona therefore affects the physicochemical properties of particles, and can influence their behavior in vivo.…”
Section: Formation Of Protein Coronasmentioning
confidence: 99%
“…[15,94,99] Therefore, to retain the targeting ability of particles in a biological environment, the goal is to better understand the formation and effects of protein coronas in order to eliminate their negative impacts on in vivo particle targeting and behavior. [21b,89c,123] Low-fouling materials (e.g., PEG, zwitterionic polymers and carbohydrates) have been extensively used to confer the carrier surface with stealth properties and can significantly reduce the amount of adsorbed proteins on the particle surface.…”
Section: Tuning the Protein Corona Through Particle Designmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Among these materials, protein-decorated Au NPs are of great importance because they can confer colloidal stability and bioactivity to Au NPs. 14,15 Au NPs can be synthesized by the chemical reduction of gold ions in the presence of a surface-capping ligand. 16 The capping ligand provides particle stabilization and an opportunity for surface modification.…”
Section: Introductionmentioning
confidence: 99%